Behavioral alterations associated with apoptosis and down-regulation of presenilin 1 in the brains of p53-deficient mice - Amson, Robert (The National Academy of Sciences, 2000)
Presenilin 1 (PS1) expression is repressed by the p53 tumor suppressor. As shown herein, wild-type PS1 is an effective antiapoptotic molecule capable of significantly inhibiting p53-dependent and p53-independent cell death. We analyzed, at the functional and molecular levels, the brains of p53 knockout mice. Surprisingly, we found that lack of p53 expression induces apoptotic brain lesions, accompanied by learning deficiency and behavioral alterations. p53-deficient mice show an unexpected overexpression of p21(waf1) with subsequent down-regulation of PS1 in their brains. This process is progressive and age-dependent. These data indicate that the p53 pathway, besides affecting tumor suppression, may play a major role in regulating neurobehavioral function and cell survival in the brain.